Conceptualisation study for using RFID as a stand-alone vehicle positioning system - Saab, Samer S. (2009)
This paper examines the possibility for using RFID technology as a complete stand-alone vehicle positioning system. The concept is based on the vehicle carrying an RFID reader, which reads RFID tags installed on the side of the vehicle path. Selection of the RFID reader, antenna and tags is studied based on the current RFID technology. A positioning system using a Kalman filter is proposed in order to estimate the vehicle position. The inputs of the proposed algorithm are the fixed distance between two consecutive tags and the erroneous measurements of the backscattered signal power propagated from nearby RFID tags. A numerical example is presented illustrating the performance of the proposed positioning system.